Peningkatan Karakter Religius dan Literasi Finansial di Pondok Pesantren An Nahdhoh Malaysia [Enhancing Religious Character and Financial Literacy at An Nahdhoh Islamic Boarding School, Malaysia] - Djazilan, M. Sukron; Nafiah, Nafiah; Mariati, Pance; Khoiriyah, Luluk (Indonesia Berdaya, 2026)
This community service initiative was carried out at An Nahdhoh Islamic Boarding School in Malaysia with the main objective of strengthening students’ religious character and financial literacy. The purposes of this program are: (1) to reinforce religious character at An Nahdhoh Islamic Boarding School, Malaysia, and (2) to provide financial literacy counseling for the students of An Nahdhoh, Malaysia. The activities were implemented by delivering education on character building and financial literacy to the students. The program employed educational and participatory approaches, including religious lectures, group discussions, financial management simulations, and personal mentoring. The implementation process began with a needs assessment, followed by the execution of community service activities, evaluation of the activities, and follow‑up actions. The results show a significant improvement. Pretest and posttest assessments indicate that both religious character and financial literacy increased from a “good” level (score 3 out of 4) to a “very good” level (score 4 out of 4). Qualitatively, positive behavioral changes were clearly observed. The students understood what was conveyed by the community service team during the educational sessions on religious character building and financial literacy. It is recommended that a financial literacy handbook for students be developed for future programs so that it can be applied in daily life at the boarding school, enabling students to become proficient in managing their finances. Abstrak. Inisiatif pengabdian masyarakat ini dilaksanakan di Pondok Pesantren An Nahdhoh, Malaysia, dengan tujuan utama meningkatkan karakter religius dan literasi keuangan siswa. Tujuan pengabdian masyarakat ini adalah 1) untuk memberikan penguatan karakter relegius di pondok pesantren An Nahdhoh Malaysia, 2) untuk memberikan penyuluhan literasi finansial santri An Nahdhoh Malaysia. Metode kegiatan ini dilakukan dengan meberikan edukasi tentang pendidikan karakter dan literasi finansial santri An Nahdhoh Malaysia. Program ini menggunakan pendekatan edukatif dan partisipatif, meliputi ceramah agama, diskusi kelompok, simulasi manajemen keuangan, serta pendampingan personal. Proses pelaksanaan dimulai dengan asesmen kebutuhan, pelaksanaan kegiatan pengabdian masyarakat dan evalasi kegiatan pengabdian masyarakat serta tindak lanjut kegiatan. Berdasarkan hasil menunjukkan peningkatan signifikan. Penilaian pretest dan posttest memperlihatkan bahwa baik karakter religius maupun literasi keuangan meningkat dari tingkat “baik” (skor 3 dari 4) menjadi “sangat baik” (skor 4 dari 4). Secara kualitatif, perubahan perilaku positif tampak jelas. Santri memahami apa yang telah di sampaikan oleh tim pengabdian masyarakat saat kegiatan edukasi pendidika karakter relegis dan literasi finansial. Rekomendasi untuk kegiatan selanjutnya perlu dibuatkan buku untuk literasi finansial santri agar bisa diterapkan dalam kehidupan di pondok pesantren sehingga santri cakap dalam mengelola keuangan.